Global evidence of persistent violations of the International Code of Marketing of Breast‐milk Substitutes: A systematic scoping review. (21st March 2022) - Becker, Genevieve E.; Zambrano, Paul; Ching, Constance; Cashin, Jennifer; Burns, Allison; Policarpo, Eva; Datu‐Sanguyo, Janice; Mathisen, Roger
Abstract: The influence of marketing on infant and young child feeding and health is well recognized, and an International Code was adopted by the World Health Assembly (WHA) in 1981 to reduce inappropriate marketing and protect breastfeeding. Yet the marketing and influencing continue. This scoping review systematically examined the published research evidence on the nature and extent of exposure to International Code violations from 1981 to August 2021. We used several search strategies involving multi‐language databases, organization websites, citation tracking, and expert consultation, to find research items meeting our inclusion criteria. We evaluated 657 items and retained 153 studies from at least 95 countries in the review. The majority of the studies ( n = 113) documenting exposure to inappropriate marketing were published since 2010. Studies reported a broad range of marketing violations targeting mothers and families, health workers, and the general public. Marketing via digital platforms and brand extension has become more frequent. The evidence shows the use of misleading and inaccurate labeling and health and nutrition claims in breach of the Code. Our review confirms that violations of the Code have not ceased and calls for renewed attention from the WHA and national governments to protect the health of children and their mothers. Abstract : Highlights: Exposure to inappropriate marketing continues across the world in health systems, public spaces, points of sale, media, emergency programs, and direct to mothers. Studies have documented the emergence of products and marketing practices designed to circumvent the Code. Labeling and health and nutrition claims were found that were misleading, inaccurate, and in breach of the Code. Evidence of marketing through social media and other digital platforms has increased over time. Future research, guidance, and policies would benefit from an accessible central repository of comprehensive and comparable measurement tools and evidence.